Effect of P impurity on NiAlΣ5 grain boundary from first-principles study - 胡雪兰 赵若汐 罗阳 宋庆功 (Chinese physics B, 2017)
First-principles calculations based on the density functional theory（DFT） and ultra-soft pseudopotential are employed to study the atomic configuration and charge density of impurity P in Ni Al Σ5 grain boundary（GB）. The negative segregation energy of a P atom proves that a P atom can easily segregate in the Ni Al GB. The atomic configuration and formation energy of the P atom in the Ni Al GB demonstrate that the P atom tends to occupy an interstitial site or substitute a Al atom depending on the Ni/Al atoms ratio. The P atom is preferable to staying in the Ni-rich environment in the Ni Al GB forming P–Ni bonds. Both of the charge density and the deformation charge imply that a P atom is more likely to bond with Ni atoms rather than with Al atoms. The density of states further exhibits the interactions between P atom and Ni atom, and the orbital electrons of P, Ni and Al atoms all contribute to P–Ni bonds in the Ni Al GB. It is worth noting that the P–Ni covalent bonds might embrittle the Ni Al GB and weakens the plasticity of the Ni Al intermetallics.